2013
DOI: 10.4319/lo.2013.58.3.1075
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus enrichment and carbon depletion contribute to high Microcystis biomass and microcystin concentrations in Ugandan lakes

Abstract: We investigated the factors influencing cyanobacterial biomass and microcystin (MC) concentrations in several Ugandan lakes from September 2008 to February 2009. We characterized thermal structure, light availability, nutrient concentrations, chlorophyll a, phytoplankton d 13 C (as an indicator of CO 2 limitation), and phytoplankton community composition and abundance as well as MC concentrations. We used these data to test several hypotheses based on previous research in temperate lakes regarding the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 52 publications
0
40
1
Order By: Relevance
“…Lake Victoria). Many of these lakes can sustain perennially high standing crops of phytoplankton (Poste et al, 2013), offering a unique opportunity to explore the influence of lake trophic status on Hg uptake and trophic transfer, and in particular, to assess the potential for eutrophication-mediated biodilution (Pickhardt et al, 2002;Herendeen and Hill, 2004;Chen and Folt, 2005;Karimi et al, 2007) of Hg in tropical African lakes. Previous studies of Hg in the food webs of several sub-Saharan African lakes (including several embayments of Lake Victoria, Lake Malawi, Lake Tanganyika, Lake Chad and several smaller lakes; Table 1) have typically reported low Hg concentrations in fish (Black et al, 2011), and Hg biomagnification ( Table 1) that falls within the range encountered in freshwater and marine systems worldwide (Lavoie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Lake Victoria). Many of these lakes can sustain perennially high standing crops of phytoplankton (Poste et al, 2013), offering a unique opportunity to explore the influence of lake trophic status on Hg uptake and trophic transfer, and in particular, to assess the potential for eutrophication-mediated biodilution (Pickhardt et al, 2002;Herendeen and Hill, 2004;Chen and Folt, 2005;Karimi et al, 2007) of Hg in tropical African lakes. Previous studies of Hg in the food webs of several sub-Saharan African lakes (including several embayments of Lake Victoria, Lake Malawi, Lake Tanganyika, Lake Chad and several smaller lakes; Table 1) have typically reported low Hg concentrations in fish (Black et al, 2011), and Hg biomagnification ( Table 1) that falls within the range encountered in freshwater and marine systems worldwide (Lavoie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Flushing of water bodies was not analysed in this meta-analysis due to the lack of detailed information for flushing rates of different water bodies. Poste et al (2013) showed that higher flushing rates of Napolean Gulf in Lake Victoria had led to a lower biomass of Microcystis compared to other less flushed sites such as Lake George and Lake Saka in Uganda. However, the rate of flushing and difference in biomass was not quantified and thus, higher flushing in combination with other factors may have caused the lower biomass of Microcystis.…”
Section: Effects Of Nutrients and Temperature On Tropical Bloomsmentioning
confidence: 99%
“…9). The lower microcystin concentration per cell in African lakes was based on a limited amount of studies and could be a result of the infrequent sampling and short time periods sampled (monthly for 1 year, Okello et al, 2010; monthly for 6 months, Poste et al, 2013). Data collected bimonthly and over a longer period of time should be more indicative of the trends.…”
Section: Effect Of Microcystis Biomass On Microcystin Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these nutrients are naturally supplied by soils to lake waters, industrial liquid waste from catchment basins, chemical fertilisers used on farms, and grey water from houses can also flow into the lakes, leading to over-nutrition. In particular, when the N/P ratio is lowered by an increase in phosphorus concentrations, the resulting cyanobacterial bloom typically causes drinking water supplied by the lake to have a foul odour (Poste et al, 2013;Ganguly et al, 2013). Although phosphorus is an essential nutrient in lake ecosystems, high concentrations can lead to over-nutrition, resulting in eutrophication and a reduction in water transparency.…”
Section: Introductionmentioning
confidence: 99%